Gender Perspectives in the Military Academic Environment - Rusu Raluca; Dragomir Isabela; Bumbuc Ștefania; Herman Ramona (Scientific Bulletin, 2022)
This paper is the result of the Military Gender Studies project. The aim of the project is to analyze the dynamics of gender perspectives in some military institutions in Europe, namely the Military Academy, Lisbon, Portugal, the University of Turin, Italy, “Vasil Levski” National Military University, Veliko Tarnovo, Bulgaria and “Nicolae Bălcescu” Land Forces Academy of Sibiu. The project started with the application of a questionnaire to military students and this paper will present part of the results obtained only in “Nicolae Bălcescu” Land Forces Academy of Sibiu, after analyzing the discrimination dimension.